Aerial biomass and primary production of herbaceous communities in a native grassland of Elyonurus muticus under annual burnings in the Pantanal, Brazil - Cardoso, Evaldo Luis; Crispim, Sandra Mara Araújo; Rodrigues, Cristina Aparecida G.; Júnior, Waldomiro Barioni (Pesquisa Agropecuaria Brasileira, 2000)
This work was conducted in a native grassland of the Pantanal, locally called "caronal" due to the dominance of Elyonurus muticus. The objectives were to evaluate the effect of annual burnings of "caronal" on the cumulative aerial biomass, aboveground net primary production (ANPP) of herbaceous communities and soil cover. Monthly data of cumulative aerial biomass were collected during two years in an area which was burned in September/95 and in August/96, and in another area which was free of burning. ANPP was estimated through differences between aerial live biomass gathered monthly. Annual burnings reduced cumulative aerial biomass about 36% in the first year and 50% in the second year. There was a tendency of reduction of cumulative aerial biomass with repetition of the burnings. The ANPP herbaceous communities in the areas free of burning and with burnings were 3,850 kg/ha and 4,980 kg/ha, in the first year, and 5,090 kg/ha and 2,880 kg/ha in the second, respectively. Thirty days after burning, the soil cover was about 30% and only four to six months after burning it was re-established as the area free of burning.